Vitamin C Promotes Apoptosis and Cell Cycle Arrest in Oral Squamous Cell Carcinoma - Zhou, Jianjun; Chen, Chen; Chen, Xiaoqing; Fei, Yifan; Jiang, Lei; Wang, Guodong (Frontiers in Oncology, 2020)
Oral squamous cell carcinoma (OSCC) is currently ranked as the eighth most prevalent type of cancer. Despite recent advances in cancer research, the 8-year survival rate for oral squamous cell carcinoma remains only 50–60%. Therefore, markers for early detection, identification of efficient chemotherapeutic agents, and post-therapeutic monitoring are the immediate needs. With this background, this study was designed to investigate the anticancer effects of vitamin C (VC) in oral squamous cell carcinoma. Our results showed that VC had an anticancer effect on the oral squamous cell lines used in this study. VC also showed an inhibitory effect on xenograft tumors in nude mice in vitro and had a synergistic effect with cisplatin to induce cell apoptosis. Mechanistically, VC caused a significant increase in the levels of reactive oxygen species (ROS), which led to induced genotoxic (DNA damage) and metabolic (ATP depletion) stresses, inhibited Bcl-2 expression, and promoted Bax expression and caspase-3 cleavage. VC also caused cell cycle arrest at the G0/G1 phase in OSCC cells, which is related to the activation of tumor suppressor p53 and cyclin-dependent kinase inhibitor p21. In conclusion, VC bears considerable therapeutic potential for the treatment of oral squamous cell carcinoma.